2022
DOI: 10.2478/mgr-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of renewable energy innovations in the Portuguese rural tourist accommodation sector

Abstract: The imperative of decarbonisation represents a great challenge for the tourist accommodation sector. This article examines the adoption of renewable energy innovations in the tourist accommodation sector of Portugal. The analysis focuses on one of the most known tourist accommodation products in the Portuguese countryside: Tourism in Rural Areas (TER). Drawing from two complementary e-mail-based surveys conducted with TER owners/managers, the results of the study show that there is a substantial gap between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
4
12
0
Order By: Relevance
“…This study finding is in line with previous research on the adoption of renewable energy technologies in hotels elsewhere worldwide (Coles, Dinan & Warren, 2015;Dalton, Lockington & Baldock, 2007;Karagiorgas et al, 2006;Knowles, Macmillan, Palmer, Grabowski & Hashimoto, 1999). It is also consistent with the findings of the author's study on the uptake of renewable energy innovations in the Portuguese rural tourist accommodation sector (Silva, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study finding is in line with previous research on the adoption of renewable energy technologies in hotels elsewhere worldwide (Coles, Dinan & Warren, 2015;Dalton, Lockington & Baldock, 2007;Karagiorgas et al, 2006;Knowles, Macmillan, Palmer, Grabowski & Hashimoto, 1999). It is also consistent with the findings of the author's study on the uptake of renewable energy innovations in the Portuguese rural tourist accommodation sector (Silva, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the statistical data analysis confirmed that market factors may either drive or obstruct the adoption of renewable energy innovations in hotels, thus validating Hypothesis 2. The latter results are in accordance not only with those of other scholars working on the drivers and barriers to the adoption of renewable energy and/or other environmental technologies in hotels in other countries (Chan et al, 2018;Dhirasasnaa & Sahin, 2021;Dhirasasnaa et al, 2020;González & León, 2001;Sardianou & Kostakis, 2020;Mahachi et al, 2015) but also with those of the previous study carried out by the author on renewable energy innovations adoption in Portugal (Silva, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations